2021
DOI: 10.3390/foods10071472
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Fields to Improve the Use of Non-Saccharomyces Starters in Red Wines

Abstract: New nonthermal technologies, including pulsed electric fields (PEF), open a new way to generate more natural foods while respecting their organoleptic qualities. PEF can reduce wild yeasts to improve the implantation of other yeasts and generate more desired metabolites. Two PEF treatments were applied; one with an intensity of 5 kV/cm was applied continuously to the must for further colour extraction, and a second treatment only to the must (without skins) after a 24-hour maceration of 17.5 kV/cm intensity, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Alternatively, the use of non-Saccharomyces strains for alcoholic fermentation and for the improvement of the sensorial profile of neutral varieties is becoming a new trend in winemaking. Certain studies have confirmed that non-Saccharomyces yeasts implant themselves better in PEF-treated must [31,32]. Consequently, higher levels of several specific metabolites of interest produced by non-Saccharomyces yeasts have been detected in wines obtained from PEF-treated musts.…”
Section: Application Of Pef For Decontamination Of Mustmentioning
confidence: 95%
“…Alternatively, the use of non-Saccharomyces strains for alcoholic fermentation and for the improvement of the sensorial profile of neutral varieties is becoming a new trend in winemaking. Certain studies have confirmed that non-Saccharomyces yeasts implant themselves better in PEF-treated must [31,32]. Consequently, higher levels of several specific metabolites of interest produced by non-Saccharomyces yeasts have been detected in wines obtained from PEF-treated musts.…”
Section: Application Of Pef For Decontamination Of Mustmentioning
confidence: 95%
“…Average residence time 0.41 s ↑extraction Phenols +23% +25% after 7 days [ 52 ] Continuous Merlot grapes >30 kV/cm, 4.7–49.4 kJ/L Flow 500 kg/h ↑extraction ↑Phenols +23−162% Shortening of cold macerations +17−636% after 24 h [ 53 ] Continuous Rondinella grapes Square-wave pulses at 1.5 kV/cm, 1, 5 and 10 μs, 2, 10 and 20 kJ/kg, 400 Hz Flow 250 L/h ↑extraction ↑Phenols +37% +30% color intensity after fermentation [ 54 ] Continuous Grenache grapes Pulses of 5 kV/cm, 63.4 kJ/kg. 1800 µS (45 pulses of 40 µS) Average residence time 0.38 s. Temperature < 32 ± 2 Flow 120 kg/h ↑extraction ↑Phenols ×1.6 ×2.2 after 24 h [ 55 ] Ultrasounds Discontinuous Tannat grape pomace. US bath: 15−60 °C, 0−100 W, 5−50 min ↑extraction ↑Phenols +50% +50% [ 56 ] Discontinuous Red grape pomace US bath: 25 °C, 160 W, 40 kHz, 30 min, 0.4 W/mL, 720 J/mL ↑extraction +59% after 5 min [ 33 ] Discontinuous Monastrell grapes US bath: 18 °C, 40 kHz, 280 W, 90 min …”
Section: Use Of High-pressure Technologies To Extract Anthocyaninsmentioning
confidence: 99%
“…Anthocyanin extraction increases in the range of 17–100% ( Table 1 ) depending on processing conditions and post-maceration time. The temperature is increased by only 2–15 °C [ 55 ], therefore it is easy to work at room temperature or under refrigerated conditions. In addition to improved anthocyanin and phenol extraction, PEFs can be used for gentle non-thermal pasteurization of the must, thus improving the implantation of non- Saccharomyces starters [ 55 ] and potentially reducing the use of SO 2 .…”
Section: Pulsed Electric Fields (Pefs) In the Extraction Of Anthocyaninsmentioning
confidence: 99%
“…UHPH is capable of producing sterilization with the elimination of yeast, bacteria, and even spores, depending on the in-valve temperature [ 85 , 93 ]. Pulsed technologies (i.e., PEFs and PL) have shown an inactivation capacity around or above 2-log for wild yeasts in grapes [ 94 , 95 , 96 ]. The antimicrobial performance of PEFs can be greatly enhanced in combination with mild temperatures (50 °C) [ 97 ].…”
Section: Increasing the Implantation Of Non- Saccharomyces As Bioprotective Tools Using Emerging Non-thermal Technologmentioning
confidence: 99%
“…The inactivation of wild yeasts by emerging non-thermal technologies in grapes or grape must is a useful technology to facilitate the implantation of non- Saccharomyces starters that can be used to control off-flavor formation. Several non-thermal technologies have shown high efficiency in increasing the implantation of non- Saccharomyces yeasts, such as HHP [ 92 ] and PEFs [ 95 ]. The high effectiveness of UHPH also makes it a leading technology not only for improving yeast implantation, but also for reducing SO 2 levels due to its ability to inactivate oxidative enzymes [ 85 ].…”
Section: Increasing the Implantation Of Non- Saccharomyces As Bioprotective Tools Using Emerging Non-thermal Technologmentioning
confidence: 99%